2019
DOI: 10.1080/21691401.2019.1628037
|View full text |Cite|
|
Sign up to set email alerts
|

Oridonin relieves hypoxia-evoked apoptosis and autophagy via modulating microRNA-214 in H9c2 cells

Abstract: Oridonin (Orid) has been diffusely applied to remedy dissimilar cancers. Howbeit, the influence of Orid in ischemic heart disease (IHD) remains imprecise. The current study uncovered the functions of Orid in hypoxia-caused apoptosis and autophagy in H9c2 cells. H9c2 cells received hypoxia and Orid manipulation, cell viability, apoptosis, apoptosis-interrelated factors and autophagy-correlative factors were appraised. After the extraordinary vectors transfections, the impacts of miR-214 inhibition on hypoxia-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Gong et al reported that Oridonin relieved hypoxia-caused apoptosis and autophagy via adjusting the PI3K/AKT/mTOR pathway through the enhancement of miR-214 in H9C2 cells. Additionally, PTEN was forecasted to be a first-hand target of miR-214 [ 27 ]. Hu et al reported that miR-214 promotes radio sensitivity by the inhibition of ATG12-mediated autophagy in colorectal cancer (CRC).…”
Section: Discussionmentioning
confidence: 99%
“…Gong et al reported that Oridonin relieved hypoxia-caused apoptosis and autophagy via adjusting the PI3K/AKT/mTOR pathway through the enhancement of miR-214 in H9C2 cells. Additionally, PTEN was forecasted to be a first-hand target of miR-214 [ 27 ]. Hu et al reported that miR-214 promotes radio sensitivity by the inhibition of ATG12-mediated autophagy in colorectal cancer (CRC).…”
Section: Discussionmentioning
confidence: 99%
“…have found oridonin could relieve hypoxia‐induced apoptosis in H9C2 cells. 40 Basically, we observed the protective effects of oridonin on endothelial cells apoptosis both in vivo and in vitro. The increased colocation of IB4 + endothelial cells and TUNEL + apoptotic cells in vehicle‐treatment tMCAO group was reversed with oridonin treatment, and in vitro, FACS results of bEND.3 cells after OGD/R also showed oridonin significantly inhibited the cell apoptosis in a concentration‐dependent manner.…”
Section: Discussionmentioning
confidence: 75%
“…have found oridonin could relieve hypoxia-induced apoptosis in H9C2 cells. 40 Emerging reports suggest that Nrf-2, as a vital nuclear transcriptional factor, shows strong anti-oxidative activity and has been widely known as a promoter to inhibit oxidative stress and the resulting inflammation. 41 Especially, the increase in Nrf-2 nuclear translocation is strongly associated with anti-oxidative stress injury via activating AKT(Ser473)/GSK3β(Ser473)/Fyn signalling pathway, 42,43 and reportedly, oridonin could exert protective effects on anti-inflammatory and anti-oxidative activities via modulating Nrf-2.…”
Section: Discussionmentioning
confidence: 99%
“…mir-214 functions as a pro-metastatic factor in malignant tumors (42), and plays a critical role in the migration and invasion of cancer cells (43)(44)(45). The present study identified a potential link between mir-214 and cadM1 in the coordination of metastasis in melanoma.…”
Section: Discussionmentioning
confidence: 99%